Experience of Intraoperative Nerve Monitoring (IONM) in thyroid surgery at Sultan Ahmad Shah Medical Centre (SASMEC) @IIUM: an interim analysis - MN, Muhammad Danial; Mahno, Noor Ezmas; AG, Muhammad Rashdan; Abdul Wahab, Azwan Halim (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Permanent recurrent laryngeal nerve injury in the expert hands account for 0.3%. Continuous intraoperative nerve monitoring (IONM) is now the current new standard in thyroid or parathyroid surgery. It is an objective tool and useful adjunct for nerve identification, preservation, and prognostication of function in thyroid and parathyroid surgeries. Materials and Methods: This is a retrospective review conducted among patients that undergone thyroid surgery with IONM. All patients underwent general anesthesia without neuromuscular blockade. Electromyogram (EMG) endotracheal tube and/or transcutaneous electromyogram electrode through thyroid cartilage (Taiwan’s method) was used. Continuous IONM with EMG data from the vagus nerve was used. Demographic data, pathological findings, comparison of post-operative complication between both methods were recorded. Descriptive analyses were performed. Results: A total of 10 cases were involved. 3 cases using solely endotracheal EMG tube. 2 cases using combined endotracheal EMG tube and Taiwan’s methods. The other 5 cases using the Taiwan’s method. 2 of our patients had hoarseness of voice post-operatively. One showed edematous mobile bilateral vocal cord while the other one had laryngopharyngeal reflux. We found that Taiwan’s method is more sensitive to nerve’s amplitude and latency compared to EMG endotracheal tube. Rotated EMG endotracheal tube especially after dissecting a large dominant one- sided thyroid nodule may result in reduced its sensitivity. Conclusion: IONM is a new standard of care in thyroid surgery, however its interpretation of data needs to be analyzed in the expert hand.